Staurosira patagonica sp. nov., a new diatom (Bacillariophyta) from southern Argentina, with a discussion on the genus Staurosira Ehrenberg - García, María Luján (2018)
We present a detailed morphological analysis by light and scanning electron microscopy of Staurosira patagonica sp. nov. from quaternary sediments of Maar Magallanes and recent sediments of the shallow lake Laguna Toro, both in Santa Cruz Province, Argentinian Patagonia. While the valve outline of this new taxon resembles Staurosira incerta, S. construens and Pseudostaurosira pseudoconstruens, it presents features (e.g., fl at valve surface, bifurcate volae and radiate striae) that set it apart from them. Staurosira patagonica sp. nov. is smaller than other small fragilarioids species. We also discuss the main characteristics of Staurosira, we provide a list of species currently included in it, and we propose several new combinations accordingly with current concepts of araphid diatom genera.